2021
DOI: 10.1155/2021/6664453
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound May Suppress Tumor Growth, Inhibit Inflammation, and Establish Tolerogenesis by Remodeling Innatome via Pathways of ROS, Immune Checkpoints, Cytokines, and Trained Immunity/Tolerance

Abstract: Background. The immune mechanisms underlying low-intensity ultrasound- (LIUS-) mediated suppression of inflammation and tumorigenesis remain poorly determined. Methods. We used microarray datasets from the NCBI GEO DataSet repository and conducted comprehensive data-mining analyses, where we examined the gene expression of 1376 innate immune regulators (innatome genes (IGs) in cells treated with LIUS. Results. We made the following findings: (1) LIUS upregulates proinflammatory IGs and downregulates metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 126 publications
1
9
0
Order By: Relevance
“…Cytokines and chemokines in the liver are soluble mediators of local and systemic inflammation ( Figure 2(a) ) [ 8 , 43 , 56 , 57 ]. To analyze liver inflammation, we used IPA and classified 53 cytokines and chemokines from 1376 innate immune genes [ 58 , 59 ] from the Innate Immunity Database [ 58 , 60 ]. Human NASH upregulated six (11.3%) and four (7.5%) out of 53 innate immune cytokines and chemokines, respectively ( Figure 2(b) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines and chemokines in the liver are soluble mediators of local and systemic inflammation ( Figure 2(a) ) [ 8 , 43 , 56 , 57 ]. To analyze liver inflammation, we used IPA and classified 53 cytokines and chemokines from 1376 innate immune genes [ 58 , 59 ] from the Innate Immunity Database [ 58 , 60 ]. Human NASH upregulated six (11.3%) and four (7.5%) out of 53 innate immune cytokines and chemokines, respectively ( Figure 2(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…We acknowledge that carefully designed in vitro and in vivo experimental models will be needed to verify all the findings. Nevertheless, our findings provide novel insights on the roles of proinflammatory cytokines and chemokines [ 58 , 59 ] and canonical secretome [ 61 , 115 , 116 ], canonical and noncanonical inflammasome pathways, TI enzymes, and lipid peroxidation enzymes in promoting NASH/NAFLD progression as well as novel targets for the future therapeutic interventions for NASH/NAFLD, metabolic diseases, transplantation, and cancers.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms include innate immune activation (11) of endothelial cells (ECs) (3,(12)(13)(14)(15) promoting EC injury (16); Ly6Chigh inflammatory mouse monocyte and CD40 + human monocyte differentiation (7,(17)(18)(19); disease reprogrammed macrophages (20)(21)(22); cytokine and secretome regulation (23)(24)(25)(26)(27)(28)(29)(30); decreased/transdifferentiated CD4 + Foxp3 + regulatory T cells (Treg) (24,(31)(32)(33)(34); and impaired vascular repairability of bone marrow-derived progenitor cells (35,36). In addition, we recently proposed new models such as intracellular organelle dangers (37) and reactive oxygen species (ROS) as an integrated sensing system for metabolic homeostasis and alarming (38), which indicated that metabolic reprogramming and dysfunction trigger mitochondrial (MT) ROS (4,(39)(40)(41)(42); caspase-1/inflammasome activation (8, 10) downregulated histone modification enzymes (43) and increased expressions of trained immunity pathway enzymes (22,39,(44)(45)(46)…”
Section: Introductionmentioning
confidence: 99%
“…Due to its vast coverage and the nature of being the first cell type to encounter any PAMPs/DAMPs in the blood circulation, the endothelium (endothelial cells, EC) [ 46 ] could function as the primary intravascular sentinel system [ [47] , [48] , [49] ]. Thus, we compared EC to prototypic innate immune cells such as macrophages [ 50 ] in 13 innate immune features, and proposed a new paradigm that EC are innate immune cells [ 2 , 3 , 51 ], which was further supported by our new paper examining the expression changes of 1311 innate immune regulatomic genes (IGs) [ 52 , 53 ] in ECs and reviews [ 54 , 55 ]. We introduced new concepts that mitochondrial reactive oxygen species (mtROS) and proton leak mediate physiological activation and pathological activation of EC [ [56] , [57] , [58] , [59] ]; ROS systems are a new integrated network for sensing homeostasis and alarming stresses [ 60 ].…”
Section: Introductionmentioning
confidence: 99%